Rise or fall? Discovering the global world trade network rise and fall under major situations - Andry Alamsyah; Dian Puteri Ramadhani; Lidya Sri Mulyani (Journal of Open Innovation: Technology, Market and Complexity, 2023)
This study aims to examine the impact of influential factors on the global trade network through long-term and short-term network analysis based on time slices. The long-term analysis examines the overall network characteristics, key players, and the most impactful events. In particular, the short-term analysis focuses on the effect of the Covid-19 pandemic on the global trade network, which was more disruptive than previous economic crises. The paper also delves into the structural changes brought about by significant events, including a comprehensive analysis of the global health crisis. The study covers the global trade network from 1995 to 2021 and comprehensively explains its evolution, especially during economic shocks and health panics. The findings show that the Covid-19 pandemic had a significant impact on the global trade network and that the state of the global economy and health are closely tied.